2015
DOI: 10.5380/ce.v20i4.41895
|View full text |Cite
|
Sign up to set email alerts
|

Autoestima De Idosos Comunitários E Fatores Associados: Estudo De Base Populacional

Abstract: AUTOESTIMA DE IDOSOS COMUNITÁRIOS E FATORES ASSOCIADOS: ESTUDO DE BASE POPULACIONAL* SELF-ESTEEM OF COMMUNITY-BASED ELDERLY AND ASSOCIATED FACTORS: A POPULATION-BASED STUDY ABSTRACT:The aim was to assess the self-esteem of community-based elderly and verify its association with socio-demographic and health variables. The epidemiological survey was held in the urban region of Uberaba, a city in the state of Minas Gerais, with 980 elderly people. The Rosenberg Self-Esteem, Katz, Lawton and Short Geriatric Depres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
5
0
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 16 publications
4
5
0
7
Order By: Relevance
“…19 In addition, a population-based study performed in the Brazilian state of Minas Gerais showed that the geriatric patients with the worst levels of self-esteem were the older ones. 10 Considering the demographic variables (sex, marital status, education, monthly income, age group), there was no association with self-esteem in the present study, which corroborates with previous findings regarding monthly income, age group, marital status, and sex. 18,19 However, other studies 10,19 found a significant association between self-esteem and education, that is, older adults with higher education showed higher self-esteem values.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…19 In addition, a population-based study performed in the Brazilian state of Minas Gerais showed that the geriatric patients with the worst levels of self-esteem were the older ones. 10 Considering the demographic variables (sex, marital status, education, monthly income, age group), there was no association with self-esteem in the present study, which corroborates with previous findings regarding monthly income, age group, marital status, and sex. 18,19 However, other studies 10,19 found a significant association between self-esteem and education, that is, older adults with higher education showed higher self-esteem values.…”
Section: Discussionsupporting
confidence: 91%
“…10 Considering the demographic variables (sex, marital status, education, monthly income, age group), there was no association with self-esteem in the present study, which corroborates with previous findings regarding monthly income, age group, marital status, and sex. 18,19 However, other studies 10,19 found a significant association between self-esteem and education, that is, older adults with higher education showed higher self-esteem values. According to the authors, the older patients with a higher education level shall have a greater sense of safety and dignity in relation to different social relationships, which may lead to greater self-esteem.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…As age increases, there is a loss of concentration, memory and vital energy 6 . Deficits in cognitive performance are one of the most frequently mentioned factors in literature, with negative implications for the self-esteem of the elderly 7 , especially memory disorders 8 .…”
Section: Introductionmentioning
confidence: 99%